Respon Kuat Tekan Hammer Test dengan Compression Test pada Beton Normal dan Beton Pasca Bakar - Arwanto, R. (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
Obtaining the concrete compression strength with the Swiss Hammer is a standard and well-known procedure.  However, the use of this apparatus on concrete exposed to physical and chemical changes due to high temperature, is questioned.  Research was conducted to validate the hammer test results on these specific concrete elements.  The investigations were executed at the Pasar Induk Wonosobo, Wonosobo’s mean market as case study.  This local market was severely burned.  The research work was done by compression strength comparison obtained from the Hammer on the field, to the tests results performed on laboratory samples. The research work proved that there was a substantial deviation in concrete compression strength obtained from the values of the Hammer on the field as compared to the cylinders tested in the laboratory.  Therefore, the Swiss Hammer was found not suitable for non-destructive compression testing on concrete elements exposed to high temperatures due to fire or burning.Keywords: concrete, hammer test, compression testPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3938[How to cite: Arwanto, R., 2006, Respon Kuat Tekan Hammer Test dengan Compression Test pada Beton Normal dan Beton Pasca Bakar, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 85-94]